Silício e metil jasmonato na indução de resistência a Spodoptera frugiperda (Lepidoptera: Noctuidae), no desenvolvimento vegetativo e estabilidade genética de plantas de arroz - Nascimento, Amanda Maria (2017)
The Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) caterpillar is a polyphagous insect pest that causes economic damage to many plant species, including rice. The use of insecticides to control S. frugiperda has been causing the selection of resistant individuals and environmental pollution, which justifies the search for alternative control methods in the management of this insect. Therefore, the aim of this study was to evaluate the effect of silicon (Si) and methyl jasmonate (MeJA) on the behavior and biology of S. frugiperda, as well as possible modifications caused by these inductors to the vegetative development and genetic stability of rice plants, aiming to provide subsidies for the management of the insect pest. To do so, the following treatments were tested: T1-Control Group (no use of Si and MeJA); T2-foliar Tween; T3- Si drench; T4- foliar MeJA and T5- Si drench + foliar MeJA. According to the results, it was verified that the use of Si and MeJA negatively affects foliar consumption, weight gain of caterpillars, the preference for oviposition and fertility of adults. The application of Si or of Si + MeJA also caused increase in height, in relative chlorophyll index, dry and fresh mass, besides favoring a greater accumulation of Si in plants. However, there was no difference in the quantity of DNA and in the variation coefficient among treatments. Thus, it was concluded that the use of Si and MeJA causes an increase in the resistance of the plant to S. frugiperda and it contributed to the vegetative development without affecting the genetic stability of rice plants.